Rancang Bangun Smoke Generator pada Kecepatan Angin Rendah dengan Wind Tunnel Rangkaian Terbuka - Arief Mukhlisin; Erwin Erwin; Slamet Wiyono (Jurnal Asiimetrik: Jurnal Ilmiah Rekayasa Dan Inovasi, 2022)
Flow Visualization is the process of making the physical flow of a fluid visible. The air fluid used is transparent, so the flow pattern must be shown by several special methods. There are three methods for visualizing flow: surface flow visualization, particle tracking method, and optical method. Turbulence is one of the most important subjects related to testing the test section in a wind tunnel, at different wind speeds turbulence levels and other flow quality parameters must be kept as close as possible to free flow conditions. The flow visualization test is carried out using a slow motion camera at speeds of 1 m/s, 2 m/s, 3 m/s, 4 m/s and 5m/s which will form a fluid flow in the form of lines of smoke coming out of the nozzle holes inside. Test section. From the research results, the authors can conclude that the flow obtained forms a laminar flow and good suction power from various wind speed variables.